2020
DOI: 10.3389/fpubh.2020.608852
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Public Perceptions on Vaccine Acceptance Using Behavioral Economics

Abstract: This study was conducted to evaluate the impact of public perceptions of vaccine safety and efficacy on intent to seek COVID-19 vaccination using hypothetical vaccine acceptance scenarios. The behavioral economic methodology could be used to inform future public health vaccination campaigns designed to influence public perceptions and improve public acceptance of the vaccine. In June 2020, 534 respondents completed online validated behavioral economic procedures adapted to evaluate COVID-19 vaccine demand in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 24 publications
1
50
0
1
Order By: Relevance
“…In this review, 28 studies depicted the sociodemographic factors associated with public attitudes toward the COVID-19 vaccination. Coherent to findings from the literature [78], the most common factors found to influence vaccine acceptance at the microlevel were age, educational level, gender, race, and income status [23][24][25][26][27][28][29][30][31][32][33][34][35][36][44][45][46][47][48][49][50][51][52][53]63,65,68,[71][72][73]. More willingness to receive a vaccine was reported in the older age group [23,25,27,31,34,35,38,53,65], while resistance, hesitancy, and lack of intention to be vaccinated emerged in the younger age group [29,35,51].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this review, 28 studies depicted the sociodemographic factors associated with public attitudes toward the COVID-19 vaccination. Coherent to findings from the literature [78], the most common factors found to influence vaccine acceptance at the microlevel were age, educational level, gender, race, and income status [23][24][25][26][27][28][29][30][31][32][33][34][35][36][44][45][46][47][48][49][50][51][52][53]63,65,68,[71][72][73]. More willingness to receive a vaccine was reported in the older age group [23,25,27,31,34,35,38,53,65], while resistance, hesitancy, and lack of intention to be vaccinated emerged in the younger age group [29,35,51].…”
Section: Discussionmentioning
confidence: 98%
“…The majority of the reviewed studies reported that men were more willing to accept a vaccine than women [28][29][30]38,48,49]. Only one study in the USA reported higher willingness among men [32]. Moreover, other factors were included, such as health condition, people with chronic diseases [29,31,49,65,73], occupation status [27,30,46,50,53,73], marital status [27,28,52], place of residence [29,51,68,73], women being pregnant [29] or having children [30], and those who have health insurance or not [30,31,36,51].…”
Section: Sociodemographic Characteristics Shaping Public Attitudes Towards Covid-19 Vaccinesmentioning
confidence: 99%
“…Our prespecified hypotheses were that (1) most health care personnel would accept vaccination, (2) safety concerns would be the predominant barrier to vaccination uptake among those delaying vaccination, (3) job responsibilities involving direct patient interaction would facilitate vaccine acceptance, and (4) that educational attainment would be associated with vaccine acceptance. Survey content was developed by the principal investigator and research team, based on a review of the literature of similar published studies, [11][12][13][14][15][16][17] to interrogate these hypotheses and control for relevant covariables. A draft of the surveys was discussed with stakeholders within the health system, university, and local county health department for comment.…”
Section: Study Population and Survey Implementationmentioning
confidence: 99%
“…[10][11][12] COVID-19 vaccine acceptance among the general population has been associated with age, sex, race, marital status, educational attainment, political ideology, trust in media/health agencies/scientists, fear of COVID-19, perceived severity of the COVID-19 pandemic, level of vaccine efficacy, duration of vaccine protection, frequency of reported adverse effects, attitudes toward vaccination in general and prior influenza vaccination. [11][12][13][14][15][16][17] An analysis using a behavioral economics approach also showed that rapid vaccine development suppressed vaccine uptake at the same level of effectiveness. 13 FDA emergency use authorization, as compared with full FDA approval, was also associated with decreased vaccine acceptance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation